Redifinisi Jihad dalam Berbangsa dan Bernegara - Ifansyah Putra; Ibnu Murtadho (Resolusi: Jurnal Sosial Politik, 2021)
Jihad as a popular term in Islam has the meaning of struggle with the intention and sincerity for good, but the meaning of jihad, which has the value of struggle, in practice has different understandings and practices between groups in Islam. This research is qualitative in nature which aims to determine the meaning of the word jihad and to find out its implementation in the life of the state in Indonesia. Library research was chosen as a data mining method, the approach used is a phenomenological approach with image theory as the blade of analysis. There are various meanings of the word jihad, some groups with a textual Islamic perspective interpret jihad as a physical struggle that can lead to bloody conflict. Contrary to that, contextual Islamic groups understand jihad as a struggle that is not only physical, but various dimensions of struggle by seeing the condition of society as a broad and more valuable jihad field. Today, jihad is interpreted more practically by applying Islamic values ​​in everyday life, such as fashion, language, social relationships and so on. This phenomenon was then popularly called "hijrah" and became a trend in middle-class Islamic societies in Indonesia.